Organoleptic Test and Total Acid Level of Buffalo Milk and Goat Milk by Using Bamboo Ampel (Bambusa vulgaris) and Bamboo Gombong (Gigantochloa verticilata). - Muhammad Amrin Siregar; Nurzainah Ginting; R. Edhy Mirwandhono; Yunilas; Tri Hesti Wahyuni (Jurnal Peternakan Integratif, 2017)
The purpose of this research is getting know the organoleptic test of buffalo milk and goat milk by using bamboo ampel (Bambusa vulgaris) and Bamboo Gombong (Gigantochloa verticilata). This research was done at Food Technology Laboratory of Agricultural Faculty of University of Sumatera Utara in May 2017 - June 2017. The design is used in this research is a complete randomized design of factorial pattern by using two factors, they are milk factor (S): (S1 / buffalo milk and S2 / Goat milk) and the second factor is bacteria (B): (B1 / without using bamboo, B2 / using bamboo Gombong, B3 / using bamboo ampel). Parameters analyzed were Color, Aroma, Flavor, Texture and Total Acid Level. The results showed that the milk curd of buffalo milk and the milk curd of goat milk using bamboo ampel and bamboo gombong gave a not significant different effect (P <0.01) on the organoleptic value of color, smell, taste, texture and total acid level. Can be known milk milk buffalo and goat milk by using bamboo ampe and bamboo gombong more than curried milk milk and goat milk without using bamboo, for the total acid content is the same as the use of bamboo gombong without using bamboo.